2020
DOI: 10.3389/fphar.2019.01598
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Hydrophilic Components in Salvia miltiorrhiza Bge. and Carthamus tinctorius L. in Rats That Underwent Cerebral Ischemia Reperfusion Using an HPLC-DAD Method

Abstract: Background: In China, the combination of herb Salvia miltiorrhiza Bge. (Danshen) and Carthamus tinctorius L. (Honghua) is an effective treatment for stroke. A previous study showed that the combination of four herbal components: danshensu (DSS), hydroxysafflor yellow A (HSYA), salvianolic acid A (SAA), and salvianolic acid B (SAB) was effective for treatment of cerebral ischemia-reperfusion (I/R) injury in rats. However, the pharmacokinetic characteristics of this formula require further investigation. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…With its anti-apoptosis and anti-in ammatory properties, SDSS offers a promising therapeutic candidate for CIRI [24][25][26]. Our study proved that SDSS prevented CIRI both in vivo and in vitro by inhibiting NLRP3mediated endothelial cells pyroptosis.…”
Section: Discussionsupporting
confidence: 57%
“…With its anti-apoptosis and anti-in ammatory properties, SDSS offers a promising therapeutic candidate for CIRI [24][25][26]. Our study proved that SDSS prevented CIRI both in vivo and in vitro by inhibiting NLRP3mediated endothelial cells pyroptosis.…”
Section: Discussionsupporting
confidence: 57%
“…Acute ischemic stroke (IS) accounts for >80% of all strokes ( Cheng et al, 2020 ). The global burden of ISs is approximately fourfold higher than hemorrhagic strokes ( Zhao et al, 2019 ). Tissue plasminogen activator (tPA) is the only Food and Drug Administration- (FDA-) approved treatment for acute IS ( Chan et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,26 Adequate evidence have demonstrated the higher morbidity and mortality rate in older adults with cerebrovascular disease. [27][28][29] Furthermore, the physical deterioration, prevalent comorbidities, and the potential psychological effects generally lead to a worse outcome in such population after a fracture. After multivariate logistic regression on total patients involved in this study, our data demonstrated that age≥80 and the number of comorbidities≥3 are independently associated with perioperative complications in fall-related fractured patients with the cerebrovascular disease while the type of cerebrovascular disease, fracture location, and comorbidities of prior fragility fracture and respiratory disease were not…”
Section: Discussionmentioning
confidence: 99%